Photovoltaic-Based Electric Tourist Boat Design to Support Island Tourism at the Labuan Bajo - Putra Pratama; Mohammad Danil Arifin (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2023)
Indonesia as an archipelagic country certainly has a great opportunity to develop the potential of the marine tourism sector. Maritime tourism in Indonesia has become a prima donna for foreign and foreign tourists, especially in Labuan Bajo. Task Island - Kelor Island - Karangan Island - Makasar Island is a new marine tourism destination that is currently being visited by many tourists. The design of electric ships based on renewable energy is expected to be able to answer the limited access between islands and the increasingly expensive depletion of fossil energy at this time. To get the size of the ship to be used, the linear programming method is used from several electric ship comparators that have been widely used. By utilizing batteries as energy storage for the propulsion of ship engines and using Photovoltaics as an energy source to operate navigation systems such as radar, radio, lights, and sonar. This ship can carry as many as 20 passengers with a route as far as 9,131.80 m. The operational time from 07.00 to 17.00 can be operated by as many as 5 ships with each ship taking 2 trips. The electric ship design principal dimension LOA = 14,00 m, LWL = 13,00 m, B = 6,00 m, H = 1,3 m, Cb = 0,236, Vops = 10 Knot, Vmax = 12 Knot, Electric Motor = 75 kW, Displacement 15,720 Ton.